Biomass potential — Theory and practice: Case example of the Czech Republic region. (December 2020) - Knápek, J.; Vávrová, K.; Králík, T.; Outrata, D.
Abstract: Biomass is considered to be a significant renewable energy source for the next one to two decades. In countries with conditions similar to the Czech Republic, biomass is even considered a dominant renewable source. The article therefore focuses on the determination of biomass potential on agricultural and forest land for energy purposes and it discusses the potential risks in determining the objective amount of biomass potential due to the ongoing climate change and the need to protect the land quality. According to current analyses, it is possible to estimate for the Czech Republic that the potential of biomass from forest stands will have to be reduced by about 60%–70% in one decade's outlook. Similarly, a reduction in the potential of residual biomass from agricultural land in the range of 10%–15% should be taken into account.